Direct Azidation of Phenols. Issue 33 (12th August 2019) - Kitamura, Mitsuru; Murakami, Kento; Koga, Tatsuya; Eto, Takashi; Ishikawa, Akihiro; Shimooka, Hirokazu; Okauchi, Tatsuo
Abstract : Direct azidation of phenols was developed. By treating chloroimidazolinium chloride 1b and sodium azide with phenol in the presence of a secondary amine in methoxyethanol, ortho ‐azidation of phenol was achieved. Abstract : Direct azidation of phenols was achieved by reaction of chloroimidazolinium cloride 1b, secondary amine, and sodium azide in methoxyethanol.